Thermal Stability Studies of Electrochemically Prepared Polyaniline Using Thermal Gravimetric Analysis - Ansari Khalkhali, R.; B. Keivani, Mohammad (Asian Journal of Chemistry, 2016)
In the current thermal studies, polyaniline (PAn) was prepared electrochemically in the presence of HCl, H2SO4 and p-toluene sulfonic acids. Thermal stabilities of polymers were then studied using TGA technique. It was found that polymer prepared by cyclic voltammetry method (CV) is more thermally stable than those prepared by constant potential (CP) method. It was also found that the nature of dopant acid has a great effect on thermal stability of the Pan.